A comparative study for management of fissure in ano with glycerin-trinitrate and lignocaine ointment: a randomized control trial - Galani, Kamlesh J.; Gadhvi, Ashwinkumar S.; Shah, Nidhi D. (International Journal of Research in Medical Sciences, 2018)
Background: Anal fissure is a very common benign anorectal disorder with significant morbidity among otherwise healthy individuals. Of all the patients coming to our OPD 15-20% have anal fissure. So there arises need to study the best and most compliant conservative treatment modality. Methods: Study was randomized, prospective, observational and longitudinal including 200 patients of age group 18-60 equally divided in 2 groups. Group A given 0.2% GTN ointment and group B given lignocaine ointment. Results: Better and early and sustained symptomatic relief was noted with GTN compared to lignocaine. 80% cases showed complete healing by 8 weeks with GTN compared to 52% healing with lignocaine. Headache was main side effect with GTN. Recurrence rate was high with lignocaine. Conclusions: Topical GTN has a statistically and clinically significant success rate for fissure healing and pain improvement at 8 weeks compared to lignocaine ointment (80% vs. 52%). It came at the cost of clinically acceptable level of morbidity (headache).